Ultrastructural and histopathologic findings after pars plana vitrectomy with a new hypersonic vitrector system. Qualitative preliminary assessment. - Salvador Pastor-Idoate; Richard Bonshek; Luciane Irion; Isaac Zambrano; Paul Carlin; Aleksandr Mironov; Paul Bishop; David McLeod; Paulo Eduardo Stanga (PLoS ONE, 2017)
PURPOSE:Preliminary assessment of a new prototype ultrasound-based hypersonic vitrector (HV) by qualitatively examining the histopathological changes in the retina and vitreous body after pars plana vitrectomy (PPV) and its ability to fragment vitreous collagen. METHODS:Fourteen porcine cadaveric eyes, 20 eyes in live swine and six human cadaveric eyes underwent PPV using the HV or a pneumatic guillotine vitrector (GV). An additional 4 porcine crystalline lenses were touched with either the HV or GV for 1 minute. Following PPV, human vitreous was removed and processed for electron microscopy (EM). Eyes and lenses were fixed and sectioned for light microscopy (LM). RESULTS:There were no macroscopic retinal or optic nerve defects associated with either HV or GV PPVs. Cadaveric retinal specimens showed separation of the inner limiting membrane (ILM) and vacuolization and fragmentation at the nerve fiber layer (NFL) and the ganglion cell layer (GCL). ILM fragmentation and separation were found after PPV in live swine with both vitrectors. Small disruptions of the posterior capsule or structural lens defects were found after HV touch. The EM analysis revealed more fragmentation of human vitreous collagen fibrils after HV compared to GV PPV. CONCLUSIONS:LM and EM analysis of retina, vitreous, and crystalline lens after PPV showed similar morphological changes using the HV or the GV. Vitreous fragmentation appeared more effective with the HV. Overall this study suggests that the HV may be a promising new technology. More work is needed to quantitatively assess its safety and efficacy.